Epidemiological characteristics of papillomavirus infection of anogenital localization in Tatarstan republic - S. T. Agliullina; Zh. G. Eremeeva; I. K. Minullin; A. Ya. Naumova; F. N. Sabaeva; I. M. Fazulzyanova (Журнал инфектологии)
Due to the high prevalence of anogenital warts, their significant economic and psychosocial burden, the lack of routine vaccination against papillomavirus infection, monitoring of the epidemiological situation for one of the common forms of papillomavirus infection – anogenital warts is relevant.The aim is to assess the epidemiological situation of anogenital warts in Tatarstan Republic for 2011–2020.Materials and methods. The study design is an observational descriptive epidemiological study. A retrospective epidemiological analysis of the incidence of anogenital warts in Tatarstan Republic for 2011–2020 was carried out. The analysis of long-term dynamics of incidence of the population as a whole and in age and sex groups is carried out. The structure of the incidence of anogenital warts was assessed. Intensive (per 100,000) and extensive morbidity rates (%) were calculated.Results. There is a decrease in the incidence of anogenital warts in Republic Tatarstan from 123,80/0000 in 2011 to 68,80/0000 in 2020. The dynamics of the incidence of anogenital warts among the female and male population had a unidirectional character – a decrease in the incidence. A comparison of incidence levels showed that the incidence of women was higher than that of men (80,40/0000 versus 55,80/0000, respectively, in 2020). The greatest incidence of anogenital warts was observed in the 18–29 age group during the observation period. The average annual incidence of anogenital warts in women aged 18–29 was 535,60/0000, in men of the same age group – 233,00/0000.Conclusion. Despite the decrease in the incidence of anogenital warts in Tatarstan Republic as a whole and in certain age and gender groups, high levels of incidence among people aged 18-29 years remain. The data obtained from the results of a retrospective analysis of the incidence of anogenital warts indicate the need to introduce routine vaccination against HPV infection, which will prevent large treatment costs, and will have a positive impact on public health indicators.